2015
DOI: 10.1371/journal.pone.0143885
|View full text |Cite
|
Sign up to set email alerts
|

Nano-TiO2 Is Not Phytotoxic As Revealed by the Oilseed Rape Growth and Photosynthetic Apparatus Ultra-Structural Response

Abstract: Recently nano-materials are widely used but they have shown contrasting effects on human and plant life. Keeping in view the contrasting results, the present study has evaluated plant growth response, antioxidant system activity and photosynthetic apparatus physiological and ultrastructural changes in Brassica napus L. plants grown under a wide range (0, 500, 2500, 4000 mg/l) of nano-TiO2 in a pot experiment. Nano-TiO2 has significantly improved the morphological and physiological indices of oilseed rape plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…The photosynthetic abilities may be reduced decrease because of increased reactive oxygen species (ROS) and lipid peroxidation, thus the chlorophyll content decreases (Hou et al, 2018). On the contrary to our result, many studies reported that TiO2-NP treatments increased photosynthetic activity and chlorophyll content of plants such as spinach (Hong et al, 2005;Yang et al, 2006), cucumber (Servin et al, 2012;Servin et al, 2013), Arabidopsis (Lenaghan et al, 2013), rapeseed (Li et al, 2015). Yang et al (2006) and Siddiqui et al (2015) reported the TiO2-NPs enhanced the chlorophyll formation and light absorption, so the photosynthetic time of chloroplast and plant growth/development increased.…”
Section: Morphological Observations and Chlorophyll Contentscontrasting
confidence: 96%
“…The photosynthetic abilities may be reduced decrease because of increased reactive oxygen species (ROS) and lipid peroxidation, thus the chlorophyll content decreases (Hou et al, 2018). On the contrary to our result, many studies reported that TiO2-NP treatments increased photosynthetic activity and chlorophyll content of plants such as spinach (Hong et al, 2005;Yang et al, 2006), cucumber (Servin et al, 2012;Servin et al, 2013), Arabidopsis (Lenaghan et al, 2013), rapeseed (Li et al, 2015). Yang et al (2006) and Siddiqui et al (2015) reported the TiO2-NPs enhanced the chlorophyll formation and light absorption, so the photosynthetic time of chloroplast and plant growth/development increased.…”
Section: Morphological Observations and Chlorophyll Contentscontrasting
confidence: 96%
“…Dang) and soybean (Yang et al, 2012 ; Singh and Lee, 2016 ), and bacterial spot disease caused by Xanthomonas perforans in tomato (Paret et al, 2013 ). Foliar spray of TiO 2 NPs increased chlorophyll content in tomato (Raliya et al, 2015a ) and oilseed rape (Li et al, 2015 ), enhanced the activity of Rubisco (Ribulose-1,5-bisphosphate carboxylase/oxygenase), and promoted net photosynthesis in Arabidopsis (Ze et al, 2011 ), spinach (Hong et al, 2005a , b ; Lei et al, 2007 , 2008 ), tomato (Qi et al, 2013 ), and basil ( Ocimum basilicum L.) (Kiapour et al, 2015 ). TiO 2 NPs treatments significantly increased crop yield or biomass of barley (Moaveni et al, 2011 ), corn (Moaveni and Kheiri, 2011 ; Morteza et al, 2013 ), mung bean ( Vigna radiate L.), snail clover ( Medicago scutellata Mil.…”
Section: Ti Improves Plant Performancementioning
confidence: 99%
“…It seems that n-TiO 2 inhibited ROS accumulation by increasing antioxidant enzymes activity. Increased antioxidant activities represent that n-TiO 2 induced stress was not severe enough to ruin the antioxidant system in the plants, rather activated it as a matter of defence and subsequently, it led to plant growth (Li et al, 2015). It was proved earlier that the presence of n-TiO 2 in the cell probably causes signal pathways, which results in regulated metabolic changes against oxidative stress (Mohammadi et al, 2014).…”
Section: Total Soluble Proteins (Tsp)mentioning
confidence: 99%
“…It was reported that up to two million tons per year of n-TiO 2 are produced worldwide (Larue et al, 2012 a). Recently, it has been indicated that different kinds of nano titanium such as anatase, rutile and brookite can influence plant growth (Aghdam et al, 2016), enzyme activity (Song et al, 2012) and photosynthetic activity (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%